2007
DOI: 10.1002/path.2094
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, organelles and ageing

Abstract: As a result of insufficient digestion of oxidatively damaged macromolecules and organelles by autophagy and other degradative systems, long-lived postmitotic cells, such as cardiac myocytes, neurons and retinal pigment epithelial cells, progressively accumulate biological 'garbage' ('waste' materials). The latter include lipofuscin (a non-degradable intralysosomal polymeric substance), defective mitochondria and other organelles, and aberrant proteins, often forming aggregates (aggresomes). An interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
211
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(216 citation statements)
references
References 109 publications
4
211
0
1
Order By: Relevance
“…1). Here a variety of organelles and proteins are degraded into their building blocks, which in turn are reutilized by the anabolic machinery of the cell following their transport to the cytosol (reviewed in Klionsky, 2007, Terman et al, 2007. From a physiological point of view, the lysosomal compartment can be looked upon as a box, built of vacuoles that constantly fuse and divide, that receives enzymes from the TGN and substrates from either the outside or the inside of the cell.…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
“…1). Here a variety of organelles and proteins are degraded into their building blocks, which in turn are reutilized by the anabolic machinery of the cell following their transport to the cytosol (reviewed in Klionsky, 2007, Terman et al, 2007. From a physiological point of view, the lysosomal compartment can be looked upon as a box, built of vacuoles that constantly fuse and divide, that receives enzymes from the TGN and substrates from either the outside or the inside of the cell.…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
“…Behl and coworkers demonstrated that BAG-3 levels are upregulated in aged neuronal cells, resulting in an increased targeting of oxidized and ubiquitylated proteins to the lysosome for disposal (Gamerdinger et al, 2009). The induction of BAG-3 mediated CASA apparently represents an important adaptation of the protein quality control system of neuronal cells to maintain proteostasis in the presence of an enhanced prooxidant and aggregation-prone milieu characteristic of aging (Terman et al, 2007).…”
Section: Casa: Chaperone-assisted Selective Autophagymentioning
confidence: 99%
“…13 This formation of hydroxyl radicals results in enhanced lipid peroxidation of membranes, and consequent LMP. 14 Scavenging iron in therapy, using metal-protein-attenuating compounds, has been proven to be beneficial in neurodegenerative diseases, thereby making inhibition of LMP and consequent necrosis an interesting therapeutic strategy. 15 The different subcellular events in necrotic signaling are elusive.…”
mentioning
confidence: 99%